Prevalence of Non-Alcoholic Fatty Liver in Type 2 Diabetes Patients - Zagdod, Asma; Kanah, Mohamed; AlNami, Nora (Sharwes Scientific Journal, 2025)
Non-alcoholic fatty liver is one of the most common liver diseases worldwide, and its occurrence is attributed to several factors, including diabetes. This study aims to determine the prevalence of non-alcoholic fatty liver among patients with type 2 diabetes in Nalut, as well as study the most important factors associated with it. During the study in Nalut, 128 people were enrolled in the diabetes clinic at Nalut Central Hospital, with 108 of them being type 2 diabetic patients and 20 randomly chosen as a control group. All individuals were measured by biometric criteria such as FBS, HbA1C, CBC, and only 44 of the participants were screened for an ultrasound for fatty liver, and the questionnaire form was filled with information regarding sex, age, duration of diabetes, and type of treatment, as well as a BMI calculation for all study participants. The results showed that 54% of diabetic patients and 45% of control group members had NAFLD according to the FIB-4 index, and that 86 % of diabetic patients and 100% of control group members had NAFLD according to the ultrasound examination result A statistical relationship was found between age (P=0.000), ALT, AST, and PLT (P=0.000), and NAFLD. No relationship was found between gender (P=0.270), BMI (P=0.507), FBS (P=0.514), and HbA1c (P=0.994) and NAFLD infection for diabetic patients participating in the study.